MPB e voz popular dos anos de 1980: Hibridismos no álbum Luz (1982) de Djavan - Hauers, Felipe Mendonça (2017)
The long play as a sound product, which brings with it a documentary value in recording processes and contexts, is the subject of research of this work. MPB music would move from the 1970s to the 1980s by a transition observed for all global urban popular music, in wich an organic approach of musical?s production would increasingly shift to a synthetic approach, with a certain hegemony of the sound product such as music itself, reordering [rearranging] the initial high-fidelity concept beyond the product recorded as a representation of live performances. The Djavan?s album Luz (1982) took with it many of the relationships that are theoretically pointed out, as well as other conditions and cultural ties that are not necessarily bounded by this theory for early 1980?s. Djavan's compositional activity proved to be indexed to MPB that emerged in the 1960s, being one of the last artists to be connected to the "catalog?s artists” of the primary MPB and counting in this album with other industrial standards of systematization inserted in a network of international cultural production quite accurate in relation to identity, reference to the live performances and diffusion generated in the Djavan?s album Luz. Systematization and balance of tracks in relation to vinyl support, international pop stars and categorical soloists, international musical production linked to North American musicians of soul music and studio, more wide diffusion sales are added to the activities of Djavan and his brazilian group Sururu de Capote, that already came in this direction conceptually, before that international production that resulted in this album. The analysis of the recorded product, along with the use of linguistics and Peircean semiotics, present good adaptability for the analysis of the popular music and the voice of the singer, taking the pattern of auditory diffusion. Luz presents some hybrid characteristics in itself, points out the vocal malleability of the brazilian popular song, indicates a new layer of international romanticism that would enter the MPB in lyrics and music, and ended with a production perspective more on support for long game and broadcasting not yet linked to the audiovisual production that would sustain the hegemony for the musical diffusion of the 1980s. The acronym MPB and its hybrid music character, who already established dialogues with pop music in the 1970s, also add possibilities for dialogue with an international (neo) romantic pop song and cosmopolitan cultural activities.